2005
DOI: 10.1074/jbc.m412911200
|View full text |Cite
|
Sign up to set email alerts
|

Dmp1-deficient Mice Display Severe Defects in Cartilage Formation Responsible for a Chondrodysplasia-like Phenotype

Abstract: Understanding the molecular mechanisms by which cartilage formation is regulated is essential toward understanding the physiology of both embryonic bone development and postnatal bone growth. Although much is known about growth factor signaling in cartilage formation, the regulatory role of noncollagenous matrix proteins in this process are still largely unknown. In the present studies, we present evidence for a critical role of DMP1 (dentin matrix protein 1) in postnatal chondrogenesis. The Dmp1 gene was orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
217
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(233 citation statements)
references
References 33 publications
15
217
1
Order By: Relevance
“…This purported biological function is supported by observations that MC3T3-E1 cells overexpressing DMP1 demonstrate an earlier onset of mineralization and the formation of a significantly larger size of the induced mineralized nodules compared to nontransfected control cells [4]. Findings from Dmp1 knockout mouse experiments and gene mutation studies on human osteomalacia strengthen the conclusion that DMP1 plays an important role in bone and dentin mineralization [5][6][7]. In addition to its direct role in biomineralization, studies indicated that DMP1 may regulate osteoblast-specific and/or odontoblast-specific genes [8,9].…”
mentioning
confidence: 70%
“…This purported biological function is supported by observations that MC3T3-E1 cells overexpressing DMP1 demonstrate an earlier onset of mineralization and the formation of a significantly larger size of the induced mineralized nodules compared to nontransfected control cells [4]. Findings from Dmp1 knockout mouse experiments and gene mutation studies on human osteomalacia strengthen the conclusion that DMP1 plays an important role in bone and dentin mineralization [5][6][7]. In addition to its direct role in biomineralization, studies indicated that DMP1 may regulate osteoblast-specific and/or odontoblast-specific genes [8,9].…”
mentioning
confidence: 70%
“…These concentrations were selected based on pilot experiments that determined saturated binding. A previous study had shown that addition of nonspecific IgG at even higher titers did not affect 45 Ca accumulation. The antibody was either added acutely on day 9, 11, or 14, or continuously with each media change starting at each of these days.…”
Section: Studies Of Effects Of Inhibitingmentioning
confidence: 83%
“…Cell culture dishes (Falcon) were from Becton Dickinson (Franklin Lakes, NJ). 45 Calcium was from Perkin/Elmer (Boston, MA). Trypsin-EDTA was from CELLGRO (Herndon, VA) and Nitex filters from Tetko Inc (Ardsley, NY).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations